Affirmative actions and gender cutting and sexuality: the invisibilization of gender and sexuality demands in the first wave of affirmative action policies in brazilian higher education - Ferreira, Sandro Augusto Silva (Revista Hipótese, 2016)
This article discusses the current context of affirmative action review / consolidation. It seeks to identify the political conditions and the correlation of forces that have made the first affirmative action policies in higher education restricted to race and class cuts, ignoring, or putting as a matter of less urgency, the demands of affirmative action in universities for women and segments of the LGBT population. Finally, she questions the reasons for the invisibility of feminist and LGBT’s in the political and academic field of affirmative action in higher education.